The Effect of Learning by Doing on Islamic Religious Education Subjects in the Project to Strengthen Pancasila Student Profiles and Work Culture to Improve Student Learning Outcomes at SMP Purnama Jakarta - Ramadanti, Ismi; Alam, Dede Rubai Misbahul; Wahab, Ahsin Abdul (Proceeding International Conference on Education, 2023)
The effect of Learning by Doing on PAI subjects in P5BK is important in improving student learning outcomes. This study aims to analyze the effect of applying the Learning by Doing method to PAI subjects in the program and evaluate its impact on student learning outcomes. The qualitative research method uses a descriptive approach by conducting observations, interviews and documentation. The subjects in this study were students and teachers who carried out P5BK in PAI learning subjects. The results showed that the application of the Learning by Doing method to PAI subjects in the P5BK had a significant effect on improving student learning outcomes. Students involved in learning that involves practical activities, collaboration, and direct experience have a better understanding of the concepts and application of religious values. It has important implications in improving the quality of Islamic Religious Education learning and creating competent and integrity students